A collective bargain : unions, organizing, and the fight for democracy - McAlevey, Jane (Ecco, an imprint of HarperCollinsPublishers, 2020)
"From longtime labor organizer Jane McAlevey, a vital call-to-arms in favor of unions, the only force capable of defending our democracy"--